Elderly-onset pulmonary sarcoidosis: A radiological approach to diagnosis - Doğan, Sevtap; Öztürk, Onural; Aydoğan Diş, Sevil; Argun Barış, Serap; Doğan, Nurettin Özgür (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background and aim: The aim was to compare the radiological and clinical characteristics of sarcoidosis between elderly and non-elderly patients. Methods: This retrospective observational study was carried out in patients with sarcoidosis. Elderly-onset sarcoidosis was defined as sarcoidosis diagnosed in patients ≥65 years-old. Patients were stratified by age (≥65 years versus <65 years) and radiological and clinical data were compared between age groups. Results: Of the 163 patients, 38 (23.3%) were in the elderly group and 125 (76.7%) were in the non-elderly group. Elderly patients more frequently demonstrated arthralgia (50% vs. 12.8%, p<0.001), coronary artery disease (15.8% vs. 2.4%, p=0.005), congestive heart failure (13.2% vs. 0.8%, p=0.003), pneumonia (7.9% vs. 0.8%, p=0.04), and pleural fluid (18.4% vs. 0.0%, p<0.001). Clinical remission was significantly more likely in younger patients than in the elderly (76.8% vs. 55.3%, p=0.01). The clinical course to chronic-progressive disease was similar in both groups (p=0.635). Radiologically, lymph nodes measuring 10-25 mm in the short axis (89.5% vs. 72.6%, p=0.032), usual interstitial pneumonia pattern (10.5% vs. 0.8%, p=0.011), and main pulmonary artery diameter above 30 mm (34.2% vs. 16.0%, p=0.014) were significantly more frequent in the elderly group. Elderly patients tended to demonstrate Scadding stage I and II sarcoidosis (39.5% and 31.6%). Conclusions: Presentation of elderly-onset sarcoidosis appears to differ from young-onset sarcoidosis. Radiologically, lymph node enlargement and the pattern of fibrosis may be distinctive.